Stenting of the Brachiocephalic Vein Following Occlusion After Coronary Artery Bypass Surgery. Issue 7 (10th June 2016) - Sandler, Nicola; Sharpin, Claire; Bhagwat, Krishna; Ma, Robert; Yii, Ming; Almeida, Aubrey
Abstract: We describe a case of left arm swelling over nine months post coronary artery bypass grafting (CABG), due to occlusion of the left brachiocephalic vein. The patient's perioperative course, diagnosis, and management of this complication are presented. doi: 10.1111/jocs.12765 (J Card Surg 2016;31:432–434)